Efektivitas Omnibus Law terhadap Perlindungan Tenaga Medis di Indonesia dalam Perbandingan dengan Sistem Hukum Malaysia - Maryanto Maryanto; Handar Subhandi Bakhtiar; Muthia Sakti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The comparison of health law between Indonesia andMalaysia covers critical aspects of the healthcare system that influence the quality of life of their citizens. This study primarily focuses on occupational health and safety (OHS) for healthcare workers. According to global data, Malaysia has a better healthcare system compared to Indonesia, as reflected in its higher ranking on the Health Care Index. In Indonesia,health law regulations often undergo changes and revisions,such as the enactment of the Omnibus Law, which consolidates various health sector regulations. However, this has raised concerns about the diminishing legal protection for healthcare workers. In contrast, Malaysia presents a more structured system, with the integration of health and labor institutions through the Department of Occupational Safety And Health (DOSH), which ensures better workplace safety and clearer standards. This research adopts a descriptive qualitative approach by analyzing legal documents such as Law Number 17 of 2023 on Health in Indonesia and the Occupational Safety and Health Act in Malaysia. The Malaysian approach is more preventive and promotive in nature, differing from Indonesia’s curative-dominated model. The study aims to compare the legal health regulations of both countries, assess their implementation effectiveness, and offer policy recommendations based on best practices applied inMalaysia to improve the quality of healthcare services inIndonesia. The findings reveal that although Indonesia has significant potential in the health sector, weak regulation implementation and supervision remain major obstacles. Therefore, a more structured and efficient regulatory reform is needed to enhance legal protection for healthcare workers and improve health services.